Analysis of Symposium Articles on Insulin Pen Devices and Alternative Insulin Delivery Methods - Dang, Devra K. (Diabetes Technology Society, 2010)
Insulin therapy is a fundamental component of diabetes management, yet there is often resistance to insulin initiation by both prescribers and patients. A barrier to insulin use is the perceived shortcomings with the traditional vial-and-syringe administration method (inconvenience, difficulty of use, association with disease and addiction, etc.). This symposium in the journal discusses the advantages of alternative insulin delivery methods, primarily insulin pen devices. Although these administration methods, especially insulin pens, have some clear advantages over the vial/syringe, there are also limitations to their use and careful patient selection and education are still needed.